Improved BTC Using Luminance Bitmap for Color Image Compression - Jun Wang; Kyeong-yuk Min; Yeun-Cheul Jeung; Jong-Wha Chong (2009 2nd International Congress on Image and Signal Processing, 2009)
Block truncation coding (BTC) is an efficient technology for color image compression. An improved BTC algorithm, luminance bit-map based BTC (LBBBTC), is presented in this paper. The LBB-BTC employs luminance bit-map to represent the three R, G and B bit-maps more exactly. Moreover, by adding 3 bits to indicate the entirely differences between Y and R, G or B bit-maps, respectively, the coding performance is improved obviously. Simulation results show that the proposed LBB-BTC performs as well as the BTC in terms of subject visual quality and PSNR, and significantly improve the compression ratio of BTC.